2020
DOI: 10.1093/cid/ciaa598
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study to Identify Clinical, Biological, and Imaging Features That Predict the Etiology of Acute Encephalitis

Abstract: Background New diagnostic tools have been developed to improve the diagnosis of infectious encephalitis. Using a prospective cohort of encephalitis patients, our objective was to identify possible clusters of patients with similar patterns among encephalitis of unknown cause, and to describe to what extent the patient’s initial presentation may be predictive of encephalitis etiology, particularly Herpes simplex virus (HSV) and Varicella-zona virus (VZV). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
1
9
1
2
Order By: Relevance
“…Varicella-zoster virus (VZV) is one of the eight herpes viruses known to cause human infections and is the second cause of acute encephalitis in France after herpes simplex virus (HSV) 1 and 2 [2,3,9]. Its incidence has grown over the last decade [10].…”
Section: Introductionmentioning
confidence: 99%
“…Varicella-zoster virus (VZV) is one of the eight herpes viruses known to cause human infections and is the second cause of acute encephalitis in France after herpes simplex virus (HSV) 1 and 2 [2,3,9]. Its incidence has grown over the last decade [10].…”
Section: Introductionmentioning
confidence: 99%
“…within 4 days) after symptom-onset [1 ▪ ]. The French multicenter ENCEIF cohort on 349 patients with encephalitis found that no initial clinical/imaging/biology pattern at admission was predictive of encephalitis cause [9]. Another analysis of 494 cases of encephalitis from the same cohort revealed that a causative agent was identified in 65.7% of cases, with viruses representing 81.8% of causative agents, especially Herpesviridae (63.6%) [10 ▪ ].…”
Section: Epidemiologymentioning
confidence: 99%
“…A few studies have investigated hospitalized adults suspected of CNS infections, 7,41 whereas other databases have focused on children or adults with encephalitis. 8,9,42…”
Section: Strategies For Studies On Cns Infectionsmentioning
confidence: 99%
“…The clinical presentation and prognosis of CNS infections has been examined in several high-quality cohort studies and databases, which have provided us with valuable knowledge. [3][4][5][6][7][8][9][10][11][12][13][14][15] However, the majority of studies in CNS infections are still limited by retrospective design and small sample sizes, or they may have relied on administrative registries and microbiological databases without access to detailed clinical data. [14][15][16][17][18] Hence, the Danish Study Group of Infections of the Brain (DASGIB) was established in 2014 and a prospective recording of all adults admitted with CNS infections at departments of infectious diseases in Denmark was initiated as of January 1, 2015.…”
Section: Introductionmentioning
confidence: 99%